Association of genetic polymorphisms with survival of pancreatic ductal adenocarcinoma patients - Rizzato, Cosmeri; Tjaden, Christin; Hackert, Thilo; Giese, Nathalia; Strobel, Oliver (Carcinogenesis, 2016)
Germline genetic variability might contribute, at least partially, to the survival of pancreatic ductal adenocarcinoma (PDAC) patients. Two recently performed genome-wide association studies (GWAS) on PDAC overall survival (OS) suggested (P < 10−5) the association between 30 genomic regions and PDAC OS. With the aim to highlight the true associations within these regions, we analyzed 44 single-nucleotide polymorphisms (SNPs) in the 30 candidate regions in 1722 PDAC patients within the PANcreatic Disease ReseArch (PANDoRA) consortium. We observed statistically significant associations for five of the selected regions. One association in the CTNNA2 gene on chromosome 2p12 [rs1567532, hazard ratio (HR) = 1.75, 95% confidence interval (CI) 1.19-2.58, P = 0.005 for homozygotes for the minor allele] and one in the last intron of the RUNX2 gene on chromosome 6p21 (rs12209785, HR = 0.88, 95% CI 0.80-0.98, P = 0.014 for heterozygotes) are of particular relevance. These loci do not coincide with those that showed the strongest associations in the previous GWAS. In silico analysis strongly suggested a possible mechanistic link between these two SNPs and pancreatic cancer survival. Functional studies are warranted to confirm the link between these genes (or other genes mapping in those regions) and PDAC prognosis in order to understand whether these variants may have the potential to impact treatment decisions and design of clinical trials.